2020
DOI: 10.2147/cmar.s270470
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pretreatment Apparent Diffusion Coefficient as a Predictor of Response to Transcatheter Arterial Chemoembolization Immediately Combined with Radiofrequency Ablation for Treatment of Solitary Large Hepatocellular Carcinoma</p>

Abstract: Purpose: To evaluate whether the pretreatment apparent diffusion coefficient (ADC) measured with diffusion weighted imaging (DWI) of tumor can be used as an imaging biomarker for predicting prognosis in solitary large hepatocellular carcinomas (HCCs) treated with transcatheter arterial chemoembolization (TACE) immediately combined with radiofrequency ablation (RFA). Patients and Methods: In this single institution retrospective study, 40 solitary large HCCs that underwent treatment with TACE immediately combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…DWI provides a variety of analytical methods, such as DWI images, ADC maps, and ADC values, which can reflect the internal changes of malignant tumors at the cellular and molecular levels, and has unparalleled advantages in noninvasive evaluation of early tumor efficacy [ 11 , 12 ]. DWI is the best method for quantitative study of microvascular perfusion and diffusion in vivo and has been successfully applied to the central nervous system [ 13 , 14 ]. DWI has been gradually used for the diagnosis of abdominal disease.…”
Section: Introductionmentioning
confidence: 99%
“…DWI provides a variety of analytical methods, such as DWI images, ADC maps, and ADC values, which can reflect the internal changes of malignant tumors at the cellular and molecular levels, and has unparalleled advantages in noninvasive evaluation of early tumor efficacy [ 11 , 12 ]. DWI is the best method for quantitative study of microvascular perfusion and diffusion in vivo and has been successfully applied to the central nervous system [ 13 , 14 ]. DWI has been gradually used for the diagnosis of abdominal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results in smaller series indicate that pre-treatment baseline ADC may be a predictor of tumor response and survival in patients treated with TACE, with lower ADC values indicating worse outcome (26,27). Tang et al found similar results for patients treated with TACE and RFA (47). Higher pre-treatment ADC values were associated with higher local tumor progression-free survival in patients with HCC treated with RFA (48).…”
Section: Discussionmentioning
confidence: 69%
“…Some previous reports indicated that ADC can predict tumor behavior in several liver malignancies. So far, in HCC, pretreatment low ADC, namely values under 1.32 × 10 -3 mm 2 /s, independently predicted poorer prognosis in patients with solitary large HCCs who have undergone transcatheter arterial chemoembolization (TACE) immediately combined with radiofrequency ablation [19]. Furthermore, low minimum ADC has been reported as a risk factor for HCC recurrence following liver transplantation (20).…”
Section: Discussionmentioning
confidence: 99%